2021
DOI: 10.1016/j.jaad.2020.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of mortality associated with systemic psoriasis treatment in the Psoriasis Longitudinal Assessment and Registry (PSOLAR): A nested case-control analysis

Abstract: Background: The effects of systemic therapy on mortality risk among patients with psoriasis are not fully understood. Objective: To evaluate the impact of systemic treatment on mortality risk in patients enrolled in the Psoriasis Longitudinal Assessment and Registry. Methods: Nested case-control analyses were performed to estimate mortality risk. Cases were defined as patients who died while participating in the Psoriasis Longitudinal Assessment and Registry. Cases were matched (1:4) with controls by age, race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“… 28 , 29 , 30 These biologics include tumor necrosis factor αinhibitors, 31 interleukin-12/23 inhibitors, 32 and interleukin-17 inhibitors, 33 , 34 , 35 which may have protective effects for AMI through suppression of systemic inflammation. 6 , 36 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 These biologics include tumor necrosis factor αinhibitors, 31 interleukin-12/23 inhibitors, 32 and interleukin-17 inhibitors, 33 , 34 , 35 which may have protective effects for AMI through suppression of systemic inflammation. 6 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Emerging data suggest that in addition to the secondary impact on cardiometabolic parameters, systemic treatment may also improve the life expectancy of psoriasis patients. The PSOLAR longitudinal study demonstrated that patients with moderate to severe psoriasis who underwent systemic therapy with biologics had a reduced risk of all-cause mortality and cardiovascular mortality when compared to those with no exposure to biologics [ 38 ]. Long-term treatment with methotrexate was also associated with a reduced risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Current registry data clearly indicate a protective effect with respect to cardiovascular events. 99 11. Some of the above questions could also benefit from machine learning and artificial intelligence.…”
Section: Where Are We Going?mentioning
confidence: 99%
“…Thus, the important question arises whether the use of antipsoriatic medication should be based only on the severity of psoriasis or also on the comorbidity profile. Current registry data clearly indicate a protective effect with respect to cardiovascular events 99 Some of the above questions could also benefit from machine learning and artificial intelligence 100,101 .…”
Section: Where Are We Going?mentioning
confidence: 99%